ANALISIS NILAI-NILAI PENDIDIKAN ISLAM MULTIKULTURAL DALAM KONTEN MEDIA SOSIAL MAJELIS TA’LIM SABILU TAUBAH GUS IQDAM - Alfi Masruro; Saifulah; M. Jamhuri (Journal Multicultural of Islamic Education, 2024)
This study aims to analyze the Values ​​of Multicultural Islamic Education in the social media content of the Majlis Ta’lim Sabilu Taubah Gus Iqdam and analyze netizen responses to the social media content of the Majlis Ta’lim Sabilu Taubah Gus Iqdam. This type of research uses library research with a content analysis approach. Data were collected using the documentation method. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this study indicate that: The Values ​​of Multicultural Islamic Education in the social media content of the Majlis Ta’lim Sabilu Taubah Gus Iqdam include (a) Tolerance, (b) Equality, (c) Humanity, (d) Helping Each Other, (e) Justice, (f) Unity and Oneness, and (g) Love for Others.